Comparing the Effectiveness of Mindfulness-Based Cognitive Behavioral Therapy and Reality Therapy on Self-Differentiation in Couples Seeking Divorce - Yahyavi Gargari, Roghayeh; Farshbaf Maneisefat, Farnaz; Mahin Etemadnia, (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The current research aimed to compare the effectiveness of mindfulness-based cognitive-behavioral therapy and reality therapy on self-differentiation in couples seeking divorce.Methods and Materials: This study was a quasi-experimental type with a pre-test, post-test, and follow-up design including a control group. The statistical population consisted of all couples seeking divorce referred by the judiciary to the psychoanalytic center of Jolfa city from spring to winter of 2022. The sample included 45 individuals who were selected using inclusion and exclusion criteria through purposive sampling. After selecting the sample members, the selected individuals were randomly (via lottery) placed into three groups of 15. After sampling, two experimental groups and one control group received group mindfulness-based cognitive-behavioral therapy in 8 sessions of 90 minutes (weekly) and group reality therapy in 8 sessions of 90 minutes (weekly), respectively, while the control group did not receive any treatment. Data were collected using the Self-Differentiation Questionnaire (DCI-SF) and analyzed using mixed ANOVA and Bonferroni post-hoc test with the help of SPSS-24.Findings: The findings indicated that there is a significant difference between the overall mean of self-differentiation in the two groups of mindfulness-based cognitive-behavioral therapy and reality therapy, with mindfulness-based cognitive-behavioral therapy having a greater impact on self-differentiation (P